CAPITAL ADEQUACY ANALYSIS AND RESILIENCE OF BANK PERKREDITAN RAKYAT (BPR) IN MALANG CITY - Satiti, Novita Ratna; Fitri, Kirana Azzora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
In the context of Indonesia's banking sector, Rural Banks (BPRs) play a vital role in supporting community development and small businesses in rural areas, though they face challenges like declining numbers, limited national economic contribution, and low capital levels. This study examines the capital adequacy of Rural Banks (BPR) in Malang City, focusing on the Capital Adequacy Ratio (CAR) and its implications for bank resilience. This quantitative research uses financial statement data from seven BPRs in Malang City during 2023 as the population and sample. The data were analyzed using descriptive statistics to assess the adequacy of capital and sensitivity to a 5% and 10% increase in Risk-Weighted Assets (RWA). The findings indicate that all BPRs maintain CARs above the minimum threshold of 12%, even under increased RWA conditions. The findings emphasize the need for robust capital management to ensure BPR resilience under varying risk scenarios. This study provides critical insights for Rural Bank managers and regulators, emphasizing the need for robust capital adequacy management to sustain operations, ensure financial stability, and mitigate risks in dynamic economic environments.